Beauty Privilege Wanita menurut Pandangan Al-Qur’an (Studi Tafsir Tematik) - Wahyu Ihsan; Maratus Saudah (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
Beauty privilege gave birth to the expression "that which is beautiful and has an attractive appearance is what is appreciated". Those who have white skin, are tall, have shiny hair, are slim, wear make-up and wear modern clothing styles, always get more respect than women who don't have these criteria. This phenomenon is caused by two factors, internal factors, namely feeling insecure when seeing other women more attractive and external factors, namely job vacancies being sought are those who have an attractive appearance. The purpose of this study is to provide an overview of true beauty and appearance according to the view of the Qur'an. In answering the problem using the approach of the verses of the Qur'an, this type of research is library research, the analysis method uses Maudhu '. The result of the research shows that there are two categories of verses that discuss Beauty privilege. First, Beauty : ar-Rūm [30]: 21, ash- Sḥaaffaat [37]: 48-49, ar-Rahmān [55]: 56, ar-Rahmān [55]: 72, al-Wāqiah [56] 35- 37, and at-Tin [95]: 4. The second category, appearance: al-A'raf [7]: 31, al-A'raf [7]: 32, an-Nahl [16]: 81, an- Nur [24]: 31, al-Ahzab [33]: 59 and al-Mudatsir [74]: 4. The meaning of beauty is always associated with an angel so that beauty according to the criteria of an angel is inner and outer beauty, beauty in appearance and character. Beauty always goes hand in hand with appearance, the ethics of good appearance according to the Qur'an is to choose clothes that are not tight, closed, not thin and not flashy in color. The Qur'an considers all women the same, that is, each has a level of beauty, the only difference being the level of piety. women are expected to always improve the quality of morals (inner beauty) and pay attention to ethics in appearance that is still neat and clean (pleasant to the eye).